2019
DOI: 10.1097/ijg.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcomes of Ahmed and Baerveldt Drainage Device Surgery for Pediatric Glaucoma Following Cataract Surgery

Abstract: Precis: In this retrospective case series, both Baerveldt and Ahmed glaucoma drainage devices resulted in good long-term outcomes in eyes with pediatric glaucoma following cataract surgery (GFCS). Background: The aim of this study was to describe the long-term safety and efficacy of primary glaucoma drainage device surgery in patients with pediatric GFCS. Methods: We retrospectively identified 28 eyes of 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…The mean time from the implantation of the drainage device to the loss of its efficacy was 41.9 ±2.1 months: 42.8 ±2.7 months for Ahmed glaucoma valve and 41.2 ±3.1 months for Baerveldt glaucoma implant (Kaplan-Meier curve) [79]. Three eyes (17.6%) required second valve implantation to control intraocular pressure [79]. A review of the literature covering a period of up to 2020 identified a small number of studies evaluating long-term outcomes of valve reimplantation in the population of children with glaucoma secondary to congenital cataract surgery [79].…”
Section: Post-cataract Surgery Glaucomamentioning
confidence: 99%
See 3 more Smart Citations
“…The mean time from the implantation of the drainage device to the loss of its efficacy was 41.9 ±2.1 months: 42.8 ±2.7 months for Ahmed glaucoma valve and 41.2 ±3.1 months for Baerveldt glaucoma implant (Kaplan-Meier curve) [79]. Three eyes (17.6%) required second valve implantation to control intraocular pressure [79]. A review of the literature covering a period of up to 2020 identified a small number of studies evaluating long-term outcomes of valve reimplantation in the population of children with glaucoma secondary to congenital cataract surgery [79].…”
Section: Post-cataract Surgery Glaucomamentioning
confidence: 99%
“…Esfandiari et al evaluated long-term safety and efficacy of surgical procedures using Ahmed and Baerveldt implants in the treatment of childhood glaucoma after cataract surgery in 28 eyes in 28 patients (16 eyes were implanted with Ahmed glaucoma valves, and 12 with Baerveldt implants). The reported incidence of glaucoma developing after congenital cataract surgery varies from 15% to 45% [79,80]. The risk factors include small corneal diameter, young age at surgery and the presence of nuclear cataract.…”
Section: Post-cataract Surgery Glaucomamentioning
confidence: 99%
See 2 more Smart Citations
“…Trabeculectomy has historically poor success rates in GFCS, precludes contact lens use (which is of great importance in aphakic eyes), and begets bleb-related complications, such as infection, leak, and over filtration [38]. Glaucoma drainage implants have demonstrated superior success rates to trabeculectomy, but also beget greater complication rates, particularly of suprachoroidal hemorrhage in the setting of hypotony, as well as keratopathy due to implant-related endothelial compensation [39][40][41][42][43]. CPC can be difficult to titrate and causes greater inflammation and carries a greater risk of phtisis [35][36][37]44].…”
Section: Introductionmentioning
confidence: 99%